Analisis Keberhasilan Sistem Taqsith Emas: Studi Empiris dari Perspektif Syariah - Saiful Bahgia (CV Kalimasada Group, 2024)
This study examines the practice of gold buying and selling on credit in Pidie Regency, Indonesia. As a precious metal, gold has various uses, from jewelry to investment, and its rising value encourages many to use it as a savings instrument. Indonesia, a major gold producer, experiences price fluctuations driven by supply, demand, and the US dollar. With evolving business practices, credit transactions have become common, including in gold trading. Using a descriptive qualitative approach, the research explores processes, actors, and market dynamics in credit-based gold transactions. The findings reveal that these transactions involve selling gold above market prices with specific payment terms, offering traders the flexibility to resell and meet capital needs quickly. Gold remains a preferred investment due to its stable value and inflation resistance, now more accessible through digital platforms. Despite installment options, gold transactions in Kota Sigli largely adhere to Sharia principles, involving either cash payments or interest-free installments where the gold is held until fully paid. This approach prevents interest-based practices, ensuring transactions align with Islamic finance principles.